50-річчя українського музею в Словаччині - Сополига, М. (Народна творчість та етнографія, 2007)
By the example of Museum of the Russian and Ukrainian Culture in Svidnik (in 2002 it became a part of Slovak National Museum) the author interrogates the history of development of Ukrainian museology in Slovakia. Together with other museums of ethnic groups this museum represents high-level national cultural policy of Slovak Republic.